ANALYSIS OF WORK CONDITIONS AND CAUSES WEAR HOLES SEPARATING SIEVES IN SERVICE (Academic journal Industrial Machine Building Civil Engineering, 2017)
Advantages and disadvantages of sieves for the crusher were considered. The research focuses on changes of the holes of the sieves toroidal shape and establishes common time to failure. The result of experimental research is to establish the durability of the separating sieves with holes design close to the wear in comparison with standard sieves. The result shows the efficiency of using sieves with toroidal form of holes similar to the natural wearing, which persists for the entire lifetime and provides high-quality completion of the separation process. The principal difference in the experimental separation of the sieves is that they are in the process of operation and wear effectively perform the function of sifting the grain mass desired fraction. The new form of holes, close to form normal wearing has led to the possibility of such profiles forming that change their shape.
Keywords: sieve; exploitation; grinding; durability; shape normal wear